Different effects of P. gingivalis LPS and E. coli LPS on the expression of interleukin-6 in human gingival fibroblasts. (July 2013) - Andrukhov, Oleh; Ertlschweiger, Sandra; Moritz, Andreas; Bantleon, Hans-Peter; Rausch-Fan, Xiaohui
Abstract Objective. Gingival fibroblasts (GFs) produce pro-inflammatory cytokines in response to stimulation with lipopolysaccharide (LPS) of Porphyromonas gingivalis, which is thought to be mediated by activation of toll-like receptors (TLR)2 and TLR4. The present study investigated the expression of interleukin (IL)-6, TLR2, and TLR4 in GFs of seven different donors upon stimulation with P. gingivalis LPS. The effects of P. gingivalis LPS were compared with those of TLR4 agonist Escherichia coli LPS and TLR2 agonist Pam3CSK4. Materials and methods. GFs were stimulated with P. gingivalis LPS, E. coli LPS or Pam3CSK4 and the expression of IL-6, TLR2 and TLR4 was measured by qPCR. The surface expression of TLR2 and TLR4 was measured by flow cytometry. Results. In GFs from three donors, P. gingivalis LPS and Pam3CSK4 induced a markedly lower increase in IL-6 expression than E. coli LPS. This was accompanied by significant down-regulation of the TLR2 and TLR4 expression. In GFs from another four donors, an increase in IL-6 expression upon stimulation with P. gingivalis LPS and Pam3CSK4 was similar or even higher than that induced by E. coli LPS. In GFs of these donors, all stimuli induced an up-regulation of both mRNA and protein expression of TLR2 and did not influence that of TLR4. Conclusions. This study suggests that P. gingivalis LPS and E. coli LPS differently regulate cytokine production in human gingival fibroblasts. Regulation of the expression level of TLR2 and TLR4 by periodontal pathogens might be an important factor controlling the inflammatory response in GFs.